INTELLECTUAL CAPITAL, COMPETITIVE ADVANTAGE, AND RETURN ON ASSETS OF SHARIA BANKS IN INDONESIA FOR DURING THE Q1 2017-Q4 2018 PERIOD - Yanti Andiani; Ari Prasetyo (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh intellectual capital terhadap return on assets dengan competitive advantage sebagai variabel intervening pada bank umum syariah di Indonesia periode Q1 2017-Q4 2018. Sampel dalam penelitian ini adalah bank umum syariah di Indonesia selama periode 2017-2018. Data dikumpulkan menggunakan metode purposive sampling dan memperoleh 10 bank umum syariah. Pendekatan yang digunakan adalah pendekatan kuantitatif dengan teknik analisis jalur (path analysis) dan menggunakan software SPSS. Hasil penelitian ini menunjukkan bahwa: 1) intellectual capital berpengaruh positif dan signifikan terhadap competitive advantage bank umum syariah. 2) intellectual capital berpengaruh positif dan signifikan terhadap return on assets bank umum syariah. 3)competitive advantage berpengaruh positif signifikan return on assets bank umum syariah. 4) competitive advantage memediasi hubungan intellectual capital terhadap return on assets pada bank umum syariah.Kata Kunci: Intellectual Capital, Competitive Advantage, Return on Assets, Bank Umum Syariah ABSTRACTThis study aims to determine the effect of intellectual capital on return on assets with competitive advantage as an intervening variable in Islamic commercial banks in Indonesia in the period Q1 2017-Q4 2018. The sample in this study is Islamic commercial banks in Indonesia during the period 2017-2018. Data were collected using a purposive sampling method and obtained 10 Islamic commercial banks. The approach used is a quantitative approach with path analysis techniques (path analysis) and using SPSS software. The results of this study indicate that: 1) intellectual capital has a positive and significant effect on the competitive advantage of Islamic banks. 2) intellectual capital has a positive and significant effect on return on assets of Islamic banks. 3). competitive advantage has a significant positive effect on Islamic banks' return on assets. 4) competitive advantage mediates the relationship of intellectual capital to return on assets in Islamic commercial banks.Keyword: Intellectual Capital, Competitive Advantage, Return on Assets, Sharia General Bank